Efektivitas Penambahan Serbuk Daun Mangrove (Sonneratia caseolaris) terhadap Kualitas dan Umur Simpan Roti Tawar : The Effectiveness of Adding Mangrove Leaf Powder (Sonneratia caseolaris) on the Quality and Shelf Life of White Bread - Sumartini, Sumartini; HarahapKurnia Sada; Luthfiyana, Novi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
White Bread is a practical choice for people for breakfast as an alternative to rice. One of the biggest problems with white bread is that it is easy to experience quality deterioration due to a short shelf life so that mold grows very quickly and the appearance of a rancid smell. One effort that can be done to prevent damage and extend the quality of white bread is the addition of natural antioxidants in the form of mangrove leaf powder (Sonneratia caseolarils). This study aims to determine the effect of adding mangrove leaf powder (SDM) on the quality, antioxidant activity, and to determine the best addition treatment in reducing the level of peroxide accumulation of white bread. This research method used a completely randomized design (CRD) which consisted of six treatments, namely the addition of SDM 0g/100g (control), 0.5g/100g, 1g/100g, 1.5g/100g, 2g/100g, and 2.5g/ 100g with three replicates. Data were analyzed by ANOVA and Duncan’s Closest Real Distance Test (JNTD) at 0.05 level. The results showed that the addition of SDM significantly increased the SDM treatment 0.5-1.50 g/100g did not significantly affect the volume and hardness of white bread but the SDM treatment of 2-2.5g/100g significantly affected the volume and texture of white bread. . The addition of HR in white bread can increase the percentage of antioxidant inhibition in white bread. The addition of SDM was proven to be effective in reducing the level of peroxide accumulation with the best treatment being the addition of 2g/100g of SDM which could reduce the level of peroxide accumulation for eight days of storage. This is because the addition of mangrove leaf powder has the potential to reduce the rate of fat oxidation and increase the role of antioxidants during the shelf life of white bread.